2020
DOI: 10.1002/star.201900293
|View full text |Cite
|
Sign up to set email alerts
|

Pasting, Rheological, and Thermal Properties and Structural Characteristics of Large and Small Arenga pinnata Starch Granules

Abstract: Arenga pinnata starch (APS) is separated into large and small size fractions. The large granules (APS-L) show a more elongated oval shape, while the small granules (APS-S) are roughly close to a round shape. The large and small granules exhibit a Maltese cross at one end of the APS granules. Both large and small fractions show C-type crystallinity, but the APS-L display a higher crystallinity and more ordered molecular structure. In addition, APS-L have higher helices content than that of APS-S. The APS-L have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…Arenga pinnata flour (APF) (main components: starch 62.4%, protein 4.7%, fat 0.4%, fiber 5.4%, and water 13.2%; RS content is 50.8%) was prepared from the pulp of sugar palm ( A. pinnata ( Wurmb. ) Merr ) cultivated in Longzhou county, Guangxi province, China, and APS (main components: starch 87.8%, fat 0.2%, protein 1.6%, fiber 0.9%, and water 9.2%; RS content is 51.2%) was isolated from the APF [ 16 , 18 ]. APRS (RS content is 51.8%) was prepared using a published method [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Arenga pinnata flour (APF) (main components: starch 62.4%, protein 4.7%, fat 0.4%, fiber 5.4%, and water 13.2%; RS content is 50.8%) was prepared from the pulp of sugar palm ( A. pinnata ( Wurmb. ) Merr ) cultivated in Longzhou county, Guangxi province, China, and APS (main components: starch 87.8%, fat 0.2%, protein 1.6%, fiber 0.9%, and water 9.2%; RS content is 51.2%) was isolated from the APF [ 16 , 18 ]. APRS (RS content is 51.8%) was prepared using a published method [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Arenga pinnata is a multipurpose palm species from which a variety of foods and beverages, timber commodities, biofibers, biopolymers, and biocomposites have been produced [ 15 ]. As an important source of starch in subtropical and tropical areas, Arenga pinnata flour (APF) is generally prepared from the pulp of AP [ 16 ]. APS has high amylose content and is an ideal preparation material for RS [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…APS granules (Fig. 2a) were composed of large and small granules with the smooth and nonporous surface (Mei, et al, 2020a). After HMT, there were no significant changes on the granular surface of APS without CS (Fig.…”
Section: Sem Analysismentioning
confidence: 96%
“…Sugar palm (Arenga pinnata) is widely distributed in Eastern India, Malaysia, Indonesia, Philippines and China (Mei et al, 2020a). It is a very important cash crop and can be used as raw material for food processing and biological compound.…”
Section: Introductionmentioning
confidence: 99%
“…The RC in inbred lines ranged from 20.25% (JS0686) to 22.02% (JH1401) (Figure 3). Studies on the starch of wheat, [39][40][41] triticale, [41] barley, [42,43] normal maize, [41,44,45] waxy maize, [44] high-amylose maize, [46,44] potato, [9] and Arenga pinnata [47] showed that large starch granules have high crystallinity. The mean RC of four inbred lines is 21.31%, which is lower than the mean value of six hybrids.…”
Section: Starch X-ray Diffraction (Xrd) Patternmentioning
confidence: 99%